2023
DOI: 10.3390/ijerph20021641
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Long Working Hours on Mental Health: Evidence from China

Abstract: Although previous studies have examined the impact of long working hours on mental health in China, they have not addressed the initial value and reverse causality issues. To bridge this gap in the literature, I conducted a dynamic longitudinal analysis to investigate the association between long working hours and the risk of mental illness nationwide. Using three-wave longitudinal data from the China Family Panel Studies conducted in 2014, 2016, and 2018, I adopted dynamic regression models with lagged long w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…The Chinese government strives for employment equality in the labor market, yet women tend to assume a greater share of family responsibilities, including childrearing, eldercare, and domestic tasks. The dual transition of enduring long work hours followed by an equivalent amount of time spent on household chores can lead to a higher incidence of work-family conflict for women, thereby exacerbating the adverse effects of prolonged working hours on them [ 55 ]. The social roles of women may also have an impact on the risk of periarthritis in women.…”
Section: Discussionmentioning
confidence: 99%
“…The Chinese government strives for employment equality in the labor market, yet women tend to assume a greater share of family responsibilities, including childrearing, eldercare, and domestic tasks. The dual transition of enduring long work hours followed by an equivalent amount of time spent on household chores can lead to a higher incidence of work-family conflict for women, thereby exacerbating the adverse effects of prolonged working hours on them [ 55 ]. The social roles of women may also have an impact on the risk of periarthritis in women.…”
Section: Discussionmentioning
confidence: 99%
“…Virtanen et al conducted a meta-analysis and concluded that long working hours were positively associated with depressive symptoms, and this association was stronger in Asian countries than in others ( 33 ). Ma’s study indicated that long working hours had positive and significant relationship with the risk of mental illness, and the effect was more significant for women, white-collar workers, and employees in micro-firms, compared with their counterparts ( 34 ). Sex-stratified analysis showed that working long hours increased the odds of depression and anxiety symptoms among females ( 35 ).…”
Section: Introductionmentioning
confidence: 99%
“…For Asian countries, Nie et al (2015) used the China Health and Nutrition Survey and found little evidence that long work hours affect either workers' health or their health-related activities. Taking the endogeneity problem more seriously, Ma (2023) conducted a dynamic panel estimation with the China Family Panel Studies in the 2010s and showed that long working hours have positive and significant effects on the risk of mental illness. Ahn (2016), using a panel dataset on workweek reduction in South Korea, showed that work-hour reduction encourages workers to engage in more healthy behaviours.…”
Section: Introductionmentioning
confidence: 99%